Formation Of Concepts About the Periodic Law and the Structure of the Electronic Shells of Atoms of Elements (Eurasian Journal of Learning and Academic Teaching, 2023)
The article is devoted to the formation of concepts about the periodic law and the structure of the electronic shells of the atoms of elements. The questions that allow students to generalize their knowledge about the structure of the atom are presented. Methodological recommendations aimed at mastering this material are given